2014
DOI: 10.1371/journal.pone.0107439
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Bisexual Behaviour among MSM Attending Intervention Sites May Help in Prevention Interventions for This Bridge to the Heterosexual Epidemic in India: Data from HIV Sentinel Surveillance

Abstract: BackgroundIndian cultural tradition demanding marriage, many MSM howsoever they self-identify are likely to be married or have sex with women. To consolidate India's HIV prevention gains, it is important to understand and address the interaction between the MSM and heterosexual epidemics in India and create specific interventions for bisexual MSM. The challenge is to identify and intervene this hard to reach population. Data from HIV Sentinel Surveillance 2011 among MSM in four Indian states were analyzed to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 15 publications
(30 reference statements)
1
18
0
Order By: Relevance
“…Mostly missing from these discussions about emerging sexual identities is the effect of relationship dynamics of MSM with their female partners, which is understood only within the scope of marriage or MSM as a bridge population for HIV infection (Asthana & Oostvogels, 2001; Dodge et al, 2016; Godbole et al, 2014; Kumta et al, 2010; Ramakrishnan et al, 2015; Setia et al, 2006; Thomas, 2009a; Thomas et al, 2009b). Heterosexual marriages are attributed to pressure on MSM stemming from the cultural emphasis on marriage (Asthana & Oostvogels, 2001; Kumta et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mostly missing from these discussions about emerging sexual identities is the effect of relationship dynamics of MSM with their female partners, which is understood only within the scope of marriage or MSM as a bridge population for HIV infection (Asthana & Oostvogels, 2001; Dodge et al, 2016; Godbole et al, 2014; Kumta et al, 2010; Ramakrishnan et al, 2015; Setia et al, 2006; Thomas, 2009a; Thomas et al, 2009b). Heterosexual marriages are attributed to pressure on MSM stemming from the cultural emphasis on marriage (Asthana & Oostvogels, 2001; Kumta et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Heterosexual marriages are attributed to pressure on MSM stemming from the cultural emphasis on marriage (Asthana & Oostvogels, 2001; Kumta et al, 2010). These married MSM lead dual lives, and their sexual identities and acknowledgement of risky sexual behaviors vary as per circumstances (Asthana & Oostvogels, 2001; Dodge et al, 2016; Godbole et al, 2014). Different identities adopted by Indian MSM in different familial and sexual scenarios, their extent of closetedness, and the influence of these behaviors on safe-sex practices remain inadequately investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The participants for the present study belong to Thane district of Maharashtra, while interestingly both of the previous studies also have representation of participants from Maharashtra. 11,14 Considering the high-risk behavior among CM-MSM reported in the present study, in the context of HIV prevalence reported in the earlier studies, there is a need to understand the impact of these high-risk behaviors among MSM, including CM-MSM and their male and female sexual partners in Thane, Maharashtra.…”
Section: Prevalence Of Hiv Between Msm Having Sex Only With Men and Mmentioning
confidence: 78%
“…11,14 Nevertheless, both the studies could not find any significant difference in the HIV prevalence between the MSM having sex with only men and MSM having sex with men and women. The participants for the present study belong to Thane district of Maharashtra, while interestingly both of the previous studies also have representation of participants from Maharashtra.…”
Section: Prevalence Of Hiv Between Msm Having Sex Only With Men and Mmentioning
confidence: 89%
See 1 more Smart Citation